The Role and Molecular Mechanism of Action of Surfactant Protein D in Innate Host Defense Against Influenza A Virus - Hsieh, I-Ni; De Luna, Xavier; White, Mitchell R.; Hartshorn, Kevan L. (Frontiers in Immunology, 2018)
Influenza A viruses (IAVs) continue to pose major risks of morbidity and mortality during yearly epidemics and periodic pandemics. The genomic instability of IAV allows it to evade adaptive immune responses developed during prior infection. Of particular concern are pandemics which result from wholesale incorporation of viral genome sections from animal sources. These pandemic strains are radically different from circulating human strains and pose great risk for the human population. For these reasons, innate immunity plays a strong role in the initial containment of IAV infection. Soluble inhibitors present in respiratory lining fluids and blood provide a level of early protection against IAV. In general, these inhibitors act by binding to the viral hemagglutinin (HA). Surfactant protein D (SP-D) and mannose-binding lectin (MBL) attach to mannosylated glycans on the HA in a calcium dependent manner. In contrast, surfactant protein A, ficolins, and other inhibitors present sialic acid rich ligands to which the HA can bind. Among these inhibitors, SP-D seems to be the most potent due to its specific mode of binding to viral carbohydrates and its ability to strongly aggregate viral particles. We have studied specific properties of the N-terminal and collagen domain of SP-D that enable formation of highly multimerized molecules and cooperative binding among the multiple trimeric lectin domains in the protein. In addition, we have studied in depth the lectin activity of SP-D through expression of isolated lectin domains and targeted mutations of the SP-D lectin binding site. Through modifying specific residues around the saccharide binding pocket, antiviral activity of isolated lectin domains of SP-D can be markedly increased for seasonal strains of IAV. Wild-type SP-D causes little inhibition of pandemic IAV, but mutated versions of SP-D were able to inhibit pandemic IAV through enhanced binding to the reduced number of mannosylated glycans present on the HA of these strains. Through collaborative studies involving crystallography of isolated lectin domains of SP-D, glycomics analysis of the HA, and molecular modeling, the mechanism of binding of wild type and mutant forms of SP-D have been determined. These studies could guide investigation of the interactions of SP-D with other pathogens.